Women's International League for Peace and Freedom At Courthouse Transit Stop Protesting Removal From Buses Their "Think Before You Register For The Draft" Signs - Watkins, Howard::::::::: (1982)
Protesters hold Women's International League for Peace and Freedom banner and banned posters above outside City Hall sign; Mike Rhodes, ?,?, Lindell Cross, Jacqueline Pillar, Barbara Gaines,?, Carol Fischer, Connie Petersen, Evo Bluestein, Geneva Bennett holding Mariah Bennett, Ernestine Leas